Analog Modeling of Landslide Dynamics: Case Study from the Andean Mesón Alto Deposit, Central Chile (∼33°40′S) - Jara-Munoz, P (Elsevier B.V., 2025)
The Mesón Alto deposit in the Central Chilean Andes (∼33°40′S) is a large-volume rock avalanche deposit (∼4.5 km3) formed in a glacial valley, presenting four distinct lithological bands whose origin is uncertain. This study employs analog modeling to investigate the influence of different kinematic variables on the deposit characteristics of landslides inspired in the Mesón Alto deposit. Field mapping has identified two primary lithological groups in the Mesón Alto deposit: andesitic fragments from the Oligo-Miocene formation and Miocene granodioritic rocks. The deposit displays a complex distribution of materials, including areas with well-sorted and poorly sorted deposits and varying grain sizes, from very large blocks to a locally significant presence of fine sediments. We developed analog models using a custom device that simulates the fluvial and glacial valley topography, varying factors such as valley geometry (U- or V-valley), opposite slope angles, and the number and proportion of landslide events. The measured parameters for comparisons included the deposit s width, length, and vertical and horizontal distances from the landslide crown to the toe. Our results highlight that variations in valley geometry and the number of events significantly influence the observed deposit structure. The study s findings provide insights into the dynamics of large-volume landslides and contribute to understanding the Mesón Alto deposit s formation. Results suggest that its complexity is primarily driven by a combination of geomorphological factors and the number of rock avalanche events: U-valley in confined conditions and two events, with the first larger than the second (70 %–30 %). Our results shed light on the processes shaping the Mesón Alto deposit and offer a framework for interpreting similar deposits in other glacial valleys worldwide, enhancing our understanding of variables that potentially influence the distribution and characteristics of landslide deposits in diverse settings. © 2024 Elsevier B.V.
Keywords: Central Andes; Landslide; Analog modeling